School location and levels of teaching effectiveness of mathematics teachers in terms of knowledge of subject matter and effective classroom communication in calabar education zone of cross river state, nigeria - Bernard Diwa, Otu; Maria Sunday, Ofie; Richard Ayuh, Ojini; Kingsley Bekom, Abang; Caroline Iserom, Ita (Global journal of educational research, 2023)
This study examined school location and the levels of teaching effectiveness of Mathematics teachers in terms of knowledge of subject matter and effective classroom communication in Calabar Education Zone of Cross River State, Nigeria. To achieve the purpose of this study, one hypothesis was formulated to guide the study. Literature related to the variables under this study were reviewed accordingly. Survey research design was adopted for the study. The census sampling technique was adopted for the study. A sample of 201 teachers were randomly selected for the study. The questionnaire was the main instrument used for data collection. To test the hypotheses independent t-test and population t-test analysis statistical technique were adopted. The .05 level of significance was used for the statistical testing of the hypotheses. The result of the analysis revealed that, school location significantly influence teaching effectiveness of Mathematics teachers in terms of knowledge of subject matter and effective classroom communication. The result also revealed that the levels of teaching effectiveness of Mathematics teachers in terms of knowledge of subject matter and effective classroom communication in Calabar Education Zone of Cross River State are significantly high. Based on the findings of the study, it was recommended that teachers should use chalk that will give a sharp contrast and easy to the students’ view, the teacher should write boldly and legibly. The teacher should face the students while explaining steps involved in calculation in mathematics, teachers should avoid blocking the students’ view of the board while writing. Also, government should not relent in the effort in sustaining best school plant planning in schools.